Evaluation of Prescription Pattern for Internal Medicines Outpatients using World Health Organization Indicators - Dinge, Fonny; Abdulah, Rizky; Sumiwi, Sri A. (Universitas Padjadjaran, Indonesia)
Rational use of drugs plays an important role in efficacy and safety. World Health Organization(WHO) developed a set of indicators to assess medicines precribing pattern. The aim ofthis study was to evaluate the rational use of drugs among internal medicines outpatients ata hospital in Papua, Indonesia, using WHO prescribing indicators. This study was a retrospectiveobservational study conducted during January-March 2014. The data were obtainedfrom patients medical prescriptions. From each prescriptions, data regarding the the totalnumber of drugs, generic, antibiotics, parenteral, and essential drugs were extracted. A totalof 2025 medical precriptions were included in this study. We found out that the averagenumber of drugs per prescription was 2.3. Majority of the prescribed drugs were generic(84.14%). The use of antibiotics, parenteral drugs, and essential drugs were 33.43%, 3.40%,and 60.13%, respectively. Polypharmacy was relatively low among the subjects. The medicinesprescribing patterns among internal medicines outpatients were in accordance withWHO recommendation.Keywords: prescribing indicator, polypharmacy, essential drugs